Educating educators with social media - Wankel, Charles (Bingley, U.K. : Emerald, 2011)
Social media are increasingly popular platforms for collaboration and quick information sharing. This volume is a collection of reports on how these technologies are being used to educate educators with social media in creative and effective ways. Social networking technologies enable the integration of students and alumni in co-curricular activities in exciting and still evolving ways. The use of wikis, blogs, LinkedIn, Facebook, Twitter, text messaging, Flickr, Delicious, YouTube, Yahoo Pipes, Diigo, Second Life, Moodle, and other Web 2.0 technologies are shown in vivid examples and insightful critiques. The processes, design, delivery and evaluation of instruction using social media are examined in detail and include such topics as: the use of social media in developing countries for new approaches to teaching as support for individual and peer-based learning; new teaching orientations premised on social media such as focused distraction; enhancing in-class participation; how instructors are increasing the technical expertise that is needed by educators to develop their own 21st century curricula projects; and creating an ecosystem for life-long learning through social media.
New directions in teaching technologies : introduction to educating educators with social media / Charles Wankel -- The birth of a social networking phenomenon / Joseph Rene Corbeil, Maria Elena Corbeil -- Facebook and education : a classroom connection? / Terri L. Towner, Caroline Lego Muñoz -- Social media for higher education in developing countries : an intercultural perspective / Malik Aleem Ahmed -- A social media approach to higher education / Marlyn Tadros -- Creating an ecosystem for life-long learning through social media : a graduate experience / Stella C.S. Porto, Lisa Blaschke, Gila Kurtz -- The networked class / Lina Morgado -- Future social learning networks at universities : an exploratory seminar setting / Nina Heinze, Wolfgang Reinhardt -- Connecting future teachers with the teachers of today / Larysa Nadolny -- Developing a pedagogy : role of the tutor in enabling student learning through the use of a Wiki / Martina A. Doolan -- Technology integration can be delicious : social bookmarking as a technology integration tool / Gloria Edwards, Barbra F. Mosley -- Public issues, private concerns : social media and course management systems in higher education / Jeremy Sarachan, Kyle F. Reinson -- Web 2.0 : information literacy, libraries, and pedagogies / Beth Martin -- Social annotation to enhance learning and assessment in higher education / David G. Lebow, Dale W. Lick, Hope J. Hartman, Campbell Dalglish, Oliver Grundmann -- Our head in the cloud : transforming work on college completion / Diana D. Woolis, Gail O. Mellow -- Enhancing in-class participation in a Web 2.0 world / Steve Rhine, Mark Bailey -- (Social) media literacy : challenges and opportunities for higher educators / Mark Gammon, Joanne White -- Social media killed the LMS : re-imagining the traditional learning management system in the age of blogs and online social networks / Danielle M. Stern, Michael D.D. Willits -- Twitter in higher education / Kay Lehmann, Lisa Chamberlin.
Includes index.
Print version record
Keywords: Education -- Professional Development; Education -- General; Education; Teachers -- Training of